2016
DOI: 10.1097/hjh.0000000000001105
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plasma aldosterone and the risk of atrial fibrillation after coronary artery bypass surgery

Abstract: We developed the preoperative 'Aldoscore' for POAF risk stratification among patients with preserved LVEF requiring elective CABG. This new tool may be helpful to identify good responders to interventions targeting the proarrhythmic and profibrotic pathways of aldosterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…Several risk factors, 27,28 biomarkers, 29,30 and genetic variants 31,32 have been investigated and linked to POAF but have not proven to be particularly sensitive in predicting which patients will develop POAF. Risk indexes that attempt to predict an individual's risk for developing POAF have been developed, 29,[33][34][35][36] but these too suffer from lack of specificity predicting which patients will develop POAF.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the LA myocardium extends beyond the atriovenous junction and over the PVs (myocardial sleeves) and PAR1 expression is not expected to be different between LA and RA based on previous reports . Total RNAs were extracted using the TRIzol reagent (Promega, Madison, Washington, USA) according to previous reported protocol . cDNAs were synthesized from 3 μg of RNA in a buffer supplied with the reverse transcriptase (Promega) containing 900 μ m dNTP (Amersham Pharmacia Biotech, Buckinghamshire, UK), 20U RNAsine (Promega), 500 ng random primers (Promega), and 200U of Moloney murine leukemia virus reverse transcriptase in a final volume of 20 μL.…”
Section: Methodsmentioning
confidence: 99%